Elastoplastic Damage Model for Concrete under Triaxial Compression and Reversed Cyclic Loading - Zhang, J.; Ma, L.; Zhang Z.X. (Проблемы прочности, 2018)
The elastoplastic damage model for concrete is elaborated that can be applied to various stress states. Построена модель упругопластического повреждения бетона, которая может использоваться при различных напряженных состояниях.